Lcz696 Alleviates Myocardial Fibrosis After Myocardial Infarction Through the sFRP-1/Wnt/β-Catenin Signaling Pathway - Liu, Jing; Zheng, Xuehui; Zhang, Chen; Zhang, Chunmei; Bu, Peili (Frontiers in Pharmacology, 2021)
Background: Lcz696 (ARNI, angiotensin receptor–neprilysin inhibitor; sacubitril/valsartan) shows an inhibitory effect on fibrosis after myocardial infarction (MI). However, the underlying signaling mechanisms are poorly understood. The Wnt/β-catenin signaling pathway is activated after MI and participates in the process of myocardial fibrosis. Here, we aimed to assess the efficacy of ARNI for alleviating myocardial fibrosis after MI and hypothesized that ARNI alleviates myocardial fibrosis by inhibiting the Wnt/β-catenin signaling pathway and overexpressing sFRP-1, an inhibitor of the Wnt/β-catenin signaling pathway. Methods: Mice randomized at 1 week post-MI were administered lcz696 (60 mg/kg, n = 21), valsartan (30 mg/kg, n = 19), or corn oil (n = 13) orally for 4 weeks, while the sham-operated group received vehicle (corn oil, n = 19). Cardiac function and extent of myocardial fibrosis were measured. Western blotting and quantitative real-time polymerase chain reaction were used to detect the expression of Wnt/β-catenin pathway-related proteins. Furthermore, primary myocardial fibroblasts were stimulated with angiotensin II (Ang II) and cultured with lcz696 and the sFRP-1 inhibitor way316606 to detect the expression of Wnt/β-catenin pathway proteins. Results: Both lcz696 and valsartan alleviated myocardial fibrosis and improved cardiac function, but lcz696 had superior efficiency compared to valsartan. Furthermore, β-catenin expression was inhibited and sFRP-1 was overexpressed after drug treatment, which could be significantly improved by lcz696 in mice. In addition, lcz696 inhibited β-catenin expression in AngII-stimulated myocardial fibroblasts, and β-catenin expression increased after the inhibition of sFRP-1. Conclusion: ARNI alleviated cardiac fibrosis and cardiac remodeling by inhibiting the Wnt/β-catenin signaling pathway. In addition, ARNI can lead to overexpression of sFRP-1, which is an inhibitor of the Wnt/β-catenin signaling pathway. These results indicate a new therapeutic target of ARNI to improve myocardial fibrosis and prevent myocardial remodeling.